Website Layanan Pengaduan Masyarakat Pada Bina Marga Kota Palangka Raya - Christian, Efrans; Pranatawijaya, Viktor Handrianus; Widiatry, Widiatry; Saputra, Muhammad Dwi (Universitas Palangka Raya, 2022)
The public complaint service website is a support system primarily for the community who wish to report road and bridge damage complaints in the Public Works Department. In handling community complaints, the Public Works Department has a mechanism for handling complaints that can be done directly or using WhatsApp applications. This results in complaint handling still being manual and not computerized. The Waterfall software development methodology was used in designing and building this system. The stages involved were: Requirements Definitions, System and Software Design, Implementation and Unit Testing, Integration and System Testing, and Operation and Maintenance. The programming language used in developing the website was PHP, the database used was MySQL, and blackbox testing was performed. After testing, the website can run its functions well, which is to manage complaint data entered into the database. The aim is for the Public Works Department to plan road and bridge construction and repairs in a more structured manner and to help with road and bridge monitoring. This website can facilitate the public in reporting the location of damaged roads and bridges using the Google Maps API, making it easier for users to determine the location of damaged roads and bridges.